Family Instability and Locus of Control in Adolescence - Frauke H. Peter; C. Katharina Spieß (The B.E. Journal of Economic Analysis & Policy, 2016)
Investigating the impact of family instability is important as more and more children experience different family changes in many industrialized countries. In this paper we examine the dynamics of family structure, looking at the potential effect of yearly maternal partnership transitions on adolescents' locus of control. We aim at combining research on family instability with research on non-cognitive skill formation. We use rich and nationwide German data to identify the relationship between family instability and adolescent locus of control. Combining entropy balancing with a novel econometric method to assess potential bias from omitted variables, we find that experiencing maternal partnership transitions is negatively associated with adolescents' belief in self-determination and that internal locus of control is reduced by about a fifth of a standard deviation among those affected, even after conditioning on a large number of covariates. This is particularly true if the transitions take place during "middle childhood".
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively
Keywords: J10; J12; J13; 330; Family Stability; Locus of Control; Matching